Pregnant women's history of childhood maltreatment and current opioid use: The mediating role of reflective functioning. (March 2020) - Macfie, Jenny; Zvara, Bharathi J.; Stuart, Gregory L.; Kurdziel-Adams, Gretchen; Kors, Stephanie B.; Fortner, Kimberly B.; Towers, Craig V.; Gorrondona, Andrea M.; Noose, Samantha K.
Highlight: Opioid users in pregnancy were less able to understand mental states than controls. Mental state understanding mediated between maltreatment and opioid use severity. Improving mental state understanding may reduce opioid use and improve parenting. Abstract: There is an association between the experience of childhood maltreatment and opioid misuse in adults, especially for women. However, we know little about this association in pregnancy, and less about processes that could be the target of interventions to help women better parent their infants. We examined reflective functioning as a putative process. Reflective functioning is the ability to interpret one's own and others' behavior in terms of underlying mental states, e.g., emotions, motivations, and beliefs. We sampled 55 pregnant women who misused opioids and 38 women at high risk due to medical factors, e.g., heart disease. We assessed maltreatment with the Maltreatment and Abuse Chronology of Exposure (MACE; Teicher & Parigger, 2015), and reflective functioning with the Reflective Functioning Questionnaire (RFQ; Fonagy et al., 2016). Maltreatment variables included the sum of severity across all subtypes, number of subtypes experienced, and severity of sexual, physical, and emotional abuse, and of neglect. We created a categorical opioid user group variable: women who used opioids in pregnancy vs. high-risk medical comparisons. We found that women who used opioids in pregnancy had poorer reflective functioning than did high-risk medical comparisons. We also created an opioid use severity scale (ranging from 0 to 3) from urine assays and history of prescribed opioids from medical records. Using Hayes (2012)'s bootstrapping PROCESS macro, we found that reflective functioning mediated the association between all maltreatment variables and opioid use severity. We discuss the results in terms of how best to intervene to improve women's reflective functioning, which may help their ability to parent.